(untitled) (Research, Society and Development, 2022)
Introduction: PET-TO students observed the scarce black representation among their peers and in the student body. In view of this, and also considering the interest in the theme of racism, they promoted the event “Occupational Therapy, Racism and Occupational Justice: looking inside”. Objective: to reflect on what, from the discussions at the event, was awakened in PET students, highlighting the importance of discussing the concept of Occupational Justice in graduation. Summary of study elements: this article presents the experience reports of 4 students, discussed in 3 topics, to facilitate the reader’s understanding of the experience: knowledge/lack of knowledge of the term Occupational Justice; self-identification and representativeness and mitigating occupational injustice. Conclusion: it is emphasized that the occupational therapist is a mitigating agent of potential occupational injustices. Therefore, as students, we question ourselves and we reflect on the importance of addressing the social determinants of occupation in graduation. In the case of the black population, which has historically been the target of numerous occupational injustices, we reinforce the need for actions and more discussions, especially within the university academy, which contribute to these individuals to fully exercise their civic and social lives, having their occupational rights guaranteed and accessible.